Fifty strategies for teaching English language learners - Herrell, Adrienne L. 4 0 16; 1944- Jordan, Michael; 5 (Upper Saddle River, New Jersey : Pearson/Merrill Prentice Hall, 2008)
Provides fifty strategies for teaching English as a secondlanguage with vocabulary and comprehension builders, communication games, and cooperative learning activities; and includes DVD.
Cover title: 50 strategies for teaching English language learners.
Includes bibliographical references.
Professional.
Keywords: 2 -- 0; 6; Study and teaching;Foreign speakers. -- English language;English as a second language; 20; 2